Mosaic Mastery Elevates Global Early Childhood Motor Skills: Penguasaan Mosaik Meningkatkan Keterampilan Motorik Anak Usia Dini Secara Global - Al Aliya, Isna Syaiyada; Iffatur Rocmah, Luluk (Indonesian Journal of Innovation Studies, 2024)
This class action research investigates the efficacy of mosaic activities with loose parts materials in enhancing fine motor skills among 5-6-year-old children at TK Dharma Wanita Persatuan Anggaswangi. Utilizing observation, interviews, and documentation, the study conducted three cycles of research, observing a significant improvement from 52.8% to 82.4% in children’s fine motor skills. These findings highlight the effectiveness of incorporating mosaic activities with loose parts materials in early childhood education, offering insights for educators and curriculum developers aiming to enrich motor skills development in young learners. Highlight: Novel Method: Enhancing fine motor skills through engaging mosaic activities. Substantial Growth: Children exhibit significant improvement in fine motor skills. Educational Relevance: Insights for integrating effective motor skill activities in curricula. Keywoard: Fine Motor Skills, Mosaic Activities, Loose Parts Materials, Early Childhood Education, Class Action Research.